1997
DOI: 10.1038/bjc.1997.179
|View full text |Cite
|
Sign up to set email alerts
|

Selection of monoclonal antibody E48 IgG or U36 IgG for adjuvant radioimmunotherapy in head and neck cancer patients

Abstract: Summary Preliminary data from recent clinical radioimmunoscintigraphy studies indicate that 99mTc-labelled murine monoclonal antibodies (MAbs) E48 and U36 have a similar ability to target squamous cell carcinoma of the head and neck (HNSCC) selectively. In the present study we describe additional aspects of murine and chimeric MAb (mMAb and cMAb) E48 and U36, which might influence the selection of one MAb for adjuvant radioimmunotherapy. To make direct comparison possible, ten patients received 11.2 ± 0.3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…False-negative observations in the present study were mostly due to the presence of small metastatic lymph nodes with minimal tumor involvement (Table 5), whether or not such small tumors are efficiently targeted by mAb U36, as previously shown in a biodistribution study with mmAb U36 (19).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…False-negative observations in the present study were mostly due to the presence of small metastatic lymph nodes with minimal tumor involvement (Table 5), whether or not such small tumors are efficiently targeted by mAb U36, as previously shown in a biodistribution study with mmAb U36 (19).…”
Section: Discussionsupporting
confidence: 74%
“…In clinical radioimmunoscintigraphy and radioimmunotherapy studies done at our institute, the potential of the CD44v6-specific murine mAb (mmAb) U36 for these purposes has been shown. Radioimmunoscintigraphy with technetium99m ( 99m Tc)-labeled mmAb U36 IgG was found to be as reliable as the radiological imaging techniques computed tomography (CT) and magnetic resonance imaging (MRI) for the detection of lymph node metastases in patients with head and neck squamous cell carcinoma (HNSCC), but the detection of tumor deposits smaller than 1 cm seemed to be a problem despite the proven accumulation of the mAb in these tumors (3). Subsequently, chimeric mAb (cmAb) U36 was tested in clinical phase I dose escalation radioimmunotherapy trials (4,5).…”
mentioning
confidence: 99%
“…For this purpose, the chimeric mAb U36 (cmAb U36) and the humanized mAb BIWA 4 (bivatuzumab), both directed against CD44v6, have been evaluated (9,10). Although not a primary objective, phase I dose escalation radioimmunotherapy studies with 186 Re-labeled cmAb U36 and 186 Re-labeled bivatuzumab showed promising antitumor effects with consistent stable disease at higher radioactivity dose levels (11 -13).…”
mentioning
confidence: 99%
“…Rolling adhesions were persistent at 1 dyn/cm 2 but weaker than those of neutrophils because 10-fold elevation of the shear stress enhanced the detachment of these cells but not of PMN from the E-selectin coated substrate (data not shown). Nevertheless, the majority of E48 cDNA-transfected 14C-CMV16 cells that accumulated on E-selectin at low flow remained adherent and continued to roll on the selectin at medium shear stress range of 5 dyn/cm 2 (Fig. 9A).…”
Section: A-e48mentioning
confidence: 99%
“…The mAb E48 recognizes an outer membrane antigen that was expressed by the majority of HNSCC. The biodistribution of the E48 mAb in HNSCC patients as well as preclinical anti-E48-based therapy experiments showed that radioimmunotherapy using this antibody as a targeting vehicle was a feasible approach for the eradication of small tumor deposits (2,3). In view of its potential importance, the mAb E48 defined antigen was characterized by cDNA cloning (4).…”
mentioning
confidence: 99%